SPONTANEOUS CLOSURE OF A MACULAR HOLE RESULTING FROM YAG LASER CAPSULOTOMY IN A 13-YEAR-OLD GIRL. Issue Volume 15:Issues 5(2021) (September 2021) - Parikh, Pooja; Day Ghafoori, Shelley; Dixit, Lena; Harper, Clio Armitage
Abstract : Purpose: To describe the novel finding of spontaneous resolution of a full-thickness macular hole resulting from YAG laser capsulotomy in a 13-year-old girl with previous history of retinal detachment repair and cataract surgery. Methods: A 13-year-old girl who had developed a macular hole after YAG laser was noted to have spontaneous resolution of the macular hole at 2-week follow-up visit with concurrent increase in visual acuity. Institutional review board was not applicable for this case. Results: Spontaneous resolution of a YAG laser–induced macular hole in a pediatric patient. Conclusion: This is a novel report in a pediatric patient of spontaneous resolution of a full-thickness macular hole induced by YAG laser capsulotomy. If a macular hole is noted after YAG capsulotomy, consideration should be given to initial close observation rather than surgical intervention as spontaneous resolution may occur. Abstract : We report the novel finding of spontaneous closure of a YAG capsulotomy–related macular hole in a pediatric patient.